Pengaruh Kesadaran Wajib Pajak, Pemahaman Wajib Pajak, Saksi Perpajakan, Dan Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak Di KPP Grogol Petamburan Jakarta Barat - Yohanes, Erico; Kristianto, Septian Bayu (Asosiasi Dosen Akuntansi Indonesia, 2023)
The level of national economy and development is one of the most important things for a country, and Indonesia is no exception. Tax is the largest source of income in Indonesia that supports and sustains the development process. However, in fact there are still several compliance problems caused by various factors. This study aims to analyze whether the factors of taxpayer awareness and comprehension, as well as sanctions and service quality of e-filing implementation have an influence on individual taxpayer compliance. The method that researcher use in this research is quantitative method. The sample in this research are individual taxpayers registered at KPP Pratama Grogol Petamburan, West Jakarta. The sampling technique is convenience sampling technique. Meanwhile, the data collection technique that researcher use is a questionnaire. The results showed that: (1) taxpayer awareness has a positive and significant effect on taxpayer compliance, (2) taxpayer comprehension has a positive and significant effect on taxpayer compliance, (3) tax sanctions have a positive and significant effect on taxpayer compliance, while (4) service quality has no effect on taxpayer compliance.